Mechanical reinforcement of PBO fibers by dicarboxylic acid functionalized carbon nanotubes through in situ copolymerization. Issue 89 (9th September 2016) - Li, Yanwei; Duan, Qian; Li, Yanhui; Hu, Zhen; Li, Jun; Song, Yuanjun; Huang, Yudong
Abstract : An optimized interfacial interaction in CNTs & PBO copolymer fibers was put into effect via dicarboxylic acids functionalized CNTs, which results in well dispersed, high reactivity and efficient load transfer between CNTs fillers and PBO matrix. Abstract : To make stronger poly( p -phenylene benzobisoxazole) (PBO) fibers, we designed and synthesized a series of CNTs & PBO copolymer fibers based on dicarboxylic acid functionalized CNTs (CNTs I–III). The aim of introducting three dicarboxylic acids including two flexible (I, II) and one rigid chain (III) functionalized CNTs is to overcome the limited dispersivity and reactivity of CNTs in the PBO polymerization system. The CNTs I–III as well as pure terephthalatic acid (TPA) were further covalently incorporated with the monomer 4, 6-diaminoresorcinol dihydrochloride (DADHC) via in situ polymerization to obtain copolymers of CNTs I & PBO, CNTs II & PBO and CNTs III & PBO, respectively. Then continuous CNTs I–III & PBO copolymer fibers have been fabricated through a dry-jet wet spinning process. The chemical structure and morphology of CNTs I–III & PBO copolymer fibers were characterized by FTIR, WAXD, SEM and TEM. The mechanical and thermal properties of CNTs I–III & PBO copolymer fibers were characterized by TG and tensile testing, compared with PBO, and the properties have been enhanced. As a result, dicarboxylic acids on CNTs improves the dispersion of CNTs in the PBO matrix, provide high reaction activity and an efficient load transfer between CNTs reinforcement and PBO matrix, which may be the main reasons for improving the mechanical and thermal properties.